Humor in Face of an Angel, by Denise Chávez: a counterhegemonic discursive tool - Franco de Araujo, Lana Beth Ayres (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2014)
The present article aims to discuss the use of humor in the fictional autobiography Face of an Angel, by U.S. writer Denise Chávez. While employing comments imbued with comicality about topics which, at first, require serious treatment – Chicanas’ social condition, marriage, religion and cultural identity -, the author, through her narrator/protagonist’s autobiographical discourse, exposes, in a critical but humorous way, characters, situations and practices that compose such a peculiar cultural universe. The caustic humor contained within the selfreferential text by Soveida Dosamantes, the narrator/protagonist of the novel in question, has as its target Chicano society, the cutouts of which are her own family and the fictional town of Agua Oscura, where the plot unfolds.